2021
DOI: 10.1093/jjfinec/nbab006
|View full text |Cite
|
Sign up to set email alerts
|

Volatility Estimation and Forecasts Based on Price Durations

Abstract: We investigate price duration variance estimators that have long been neglected in the literature. In particular, we consider simple-to-construct non-parametric duration estimators, and parametric price duration estimators using autoregressive conditional duration specifications. This paper shows (i) how price duration estimators can be used for the estimation and forecasting of the integrated variance of an underlying semi-martingale price process and (ii) how they are affected by discrete and irregular spaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 71 publications
1
19
2
Order By: Relevance
“…Therefore, the measurement of instantaneous volatility lies in estimation of the intensity function associated with the process of δ−price changes, i.e., λ δ (t; F t ). A similar result is obtained in [4,5,17].…”
Section: Instantaneous Volatility Measurement Use Price Durationsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the measurement of instantaneous volatility lies in estimation of the intensity function associated with the process of δ−price changes, i.e., λ δ (t; F t ). A similar result is obtained in [4,5,17].…”
Section: Instantaneous Volatility Measurement Use Price Durationsupporting
confidence: 87%
“…Cho and Frees [14] initiated a discussion of using price duration as volatility measurement, and Gerhard and Hautsch [15] formally proposed a volatility estimator based on price durations. Tse and Yang [16] developed duration-based variance estimators using ACD specifications, and recently, Hong et al [17] proposed a non-parametric duration-based estimator and concluded that the duration-based volatility estimators are more efficient than noise-robust realized volatility estimators. Furthermore, some papers focus on modeling the intensity function itself.…”
Section: Introductionmentioning
confidence: 99%
“…where 1 6 ðδ=Y t N Þ 2 is the end-of-day bias correction. We follow Hong et al (2021) and implement the average of a range of NPDV estimators defined as follows:…”
Section: Average Version Of Npdv (Anp)mentioning
confidence: 99%
“…Our baseline results, as well as this interesting empirical evidence, raise an obvious question: Theoretically, the durationbased estimators are designed to handle market microstructure noises and large jumps and avoid potential biases in the local volatility estimate. Hence, how can we rationalize their poorer empirical performance in China given the evidence in Andersen et al (2009) and Hong et al (2021) based on US data? Our second contribution is that we undertake a comprehensive set of simulation exercises to gain further insight into these estimators and explore, specifically, whether it is the occasional extreme level of volatility in the Chinese market that leads to the different forecasting performances.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation